(untitled) (ModaPalavra e-periódico, 2010)
In view of the considerations made in the field of creativity and music and to a positive result in the fashion design, this research aims to aggregate information and practices associated with creative and music. Thus, the study includes a review of the music influence in the process of creating in the classroom. For this was made a field research with graduate students in the course of design, where the music was used as a stimulus for activities in class. The result found was a positive response to musical stimuli by most participants. Thus, this study concludes that the music can and should be used to stimulate the creativity.